(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Liver disease (LD) is one of the main causes of mortality and modality in worldwide. Around 500 million people worldwide are thought to have chronic hepatitis infections, which cause over a million deaths a year. Treatments for LD must be developed with a new approach to cure or prevent the progression of the disease without any consequences. Currently, this study's purpose is to examine and confirm the methanolic extract of Bergenia Ciliata root’s ability to protect rats from ethanol induced hepatotoxicity. Wistar rats were administered 1 cc of 30% ethyl alcohol in all the groups except the normal control P.O. once a day for 40 days in order to cause hepatoxicity. After confirmation of LD, the methanolic extract of Bergenia ciliata (MEBC) roots and the standard drug silymarin (0.1 g/kg, b.w., orally) were given twice daily for 21 days. Liver weight, body weight, Serum liver enzymes like SGPT, SGOT, serum ALP, total protein, albumin, and antioxidant enzymes were assayed to investigate the hepatoprotective effect, followed by liver histopathology to evaluate the hepatic architecture and all alignments and inflammatory cells. The protective markers of all the rats treated with alcohol showed a substantial increase, and the rats administered MEBC showed a remarkable recovery towards an almost normal level. These findings suggest that MEBC protected the structural integrity of the hepatocellular membrane and ethanol-damaged liver cells cellular architecture, which was supported by histological analysis. The present study demonstrates that the methanolic extract Bergenia Ciliata roots possess hepatoprotective property.